2005
DOI: 10.1002/chin.200531066
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Synthesis of Propargylamines via C—H Activation Catalyzed by Copper(I) in Ionic Liquids.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Independently, we found that the three-component addition of aldehyde, alkyne, and secondary amines can be catalyzed by CuI under solventless conditions with microwave irradiation . Alper showed that such a reaction is highly effective in ionic liquids . Formaldehyde as substrate for CuI-catalyzed A 3 coupling in aqueous solution has been reported recently.…”
Section: Addition Of Terminal Alkyne To Imine Tosylimine Iminium Ion ...mentioning
confidence: 87%
“…Independently, we found that the three-component addition of aldehyde, alkyne, and secondary amines can be catalyzed by CuI under solventless conditions with microwave irradiation . Alper showed that such a reaction is highly effective in ionic liquids . Formaldehyde as substrate for CuI-catalyzed A 3 coupling in aqueous solution has been reported recently.…”
Section: Addition Of Terminal Alkyne To Imine Tosylimine Iminium Ion ...mentioning
confidence: 87%
“…However, during the course of the reaction, most of these catalytic systems suffer from a loss of the costly or hazardous catalysts. In order to achieve recyclable catalysts, Ag(I) and Cu(I) in ionic liquids have been developed by Li et al 29 and Park et al, 37 respectively. Kidwai et al 38 reported gold nanoparticles as reusable catalysts, and Corma et al 39 developed CeO 2 and ZrO 2 -stabilized Au(III) as efficient catalysts for A3 coupling reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ultrasound can also be used for such reactions in water [118]. Such a reaction was shown by Alper et al in ionic liquids [119].…”
Section: Catalytic Nucleophilic Additions Via Ch Reactionmentioning
confidence: 95%